Reading–writing disorder in children with idiopathic epilepsy - Germanò, Eva; Gagliano, Antonella; Arena, Claudia; Cedro, Clemente; Vetri, Luigi; Operto, Francesca Felicia; Pastorino, Grazia Maria Giovanna; Marotta, Rosa; Roccella, Michele (Epilepsy & behavior, 2020)
Several studies have documented learning disabilities (LDs) in subjects with epilepsy, who have been shown to be at greater risk of mild neuropsychological damage, with the consequent risk of academic failure. This retrospective study aimed to investigate the peculiarities of reading and writing disorders in subjects with idiopathic epilepsy. The reading and writing performance of 35 children affected by reading and writing disorders and idiopathic epilepsy (R/WD + E group) has been compared with the performance of 37 children with only reading and writing disorders (R/WD group). A comparison group of 22 typical developing healthy children (TDC group) was also included in the study. As expected, the TDC group reached better performances in the reading and writing tests administered. Between R/WD + E and R/WD groups, there was a substantial analogy in reading and writing disabilities. The differences between the two clinical groups concern writing ability in sentences dictation and verbal and visuospatial short-term memory in digit span and memory-for-location (MFL) tests.